Strategies to Mitigate Chemotherapy-Related Cardiotoxicities in Triple-Negative Breast Cancer - Feliz Mosquea , Yismeilin R (Wake Forest University, 2024)
Triple-negative breast cancer (TNBC) is one of the most highly aggressive breast cancer types that predominantly affects young and minority women. TNBC patients are more likely to receive cytotoxic chemotherapy regimens since they have limited targeted options. This results in severe side effects resulting in chronic cardiac dysfunction. Currently, there are limited options for the treatment of cardiotoxicity that do not interfere with the anti-cancer action of chemotherapy drugs. Consequently, there is an urgent need to find new strategies that decrease the off-target effects of chemotherapy without compromising oncologic efficacy. Anthracycline (DOX) is a very effective chemotherapeutic agent; however, it is the most harmful toxic agent used to treat different types of cancer, including breast cancer.
Keywords: Cadio-Oncology; Chemotherapy-Cardiotoxicity; Inositol-Requiring Enzyme-1 (IRE1); Mitochondria Respiration; Obesity; Unfolded Protein Response